Moisture transport patterns over the Northeastern Tibetan Plateau revealed by tree-ring δ18O records - Kai Wang; Xiaohua Gou; Takeshi Nakatsuka; Yiran Zhang; Jiangzhou Feng; Linlin Gao; Tao Wang; Yang Deng; Zhen Li; Kaixuan Yang; Xuan Li; Chongshan Wang; et al. (Journal of Hydrology, 2026)

Atomic-level regulation of peroxymonosulfate activation on coal gangue: Toward controllable catalytic pathways and enhanced environmental resilience - Lixin Li; Peijiang Han; Tao Qin; Bo Zhang; Linlin Huang; Xue Dong; Qingju Tang; Xin Zhao; Fengxia Deng (Environmental Research, 2026)

UniPept: A Universal Model for Predicting Peptide Properties Based on Atom-Residue Dual-Scale Integration - Haoshuang Wu; Yu Deng; Zhen Li; Mingming Qi; Yanshi Wei; Linlin Zhuo; Quan Zou; Wenqian Zhang (Interdisciplinary Sciences: Computational Life Sciences, 2026)

Wave-driven core-shell structured cathode SMESs for remediation of phenanthrene and pyrene-contaminated offshore sediments - Haobo Yu; Boyue Liu; Hongying Yuan; Yankai Huang; Yinghao Huang; Tengfei Yuan; Linlin Li; Qi Deng; Jie Li (Journal of Hazardous Materials, 2026)

Positive covariance between temperature and precipitation affects dendroclimatological reconstructions - Linlin Gao; Tatiana Bebchuk; Clive Oppenheimer; Timothy J. Osborn; Jan Esper; Mirek Trnka; Xiaohua Gou; Yang Deng; Ulf Büntgen (Global and Planetary Change, 2026)

GAC-YOLO: A Pomegranate Disease Rapid Detection Method with Multi-Scale Feature Enhancement for an Orchard Inspection Robot - Shenghui Fu; Yongchang Deng; Shuangxi Liu; Rongwei Li; Yuefeng Du; Linlin Sun; Hongjian Zhang; Tao Xu; Wen Zhang (Applied Fruit Science, 2026)

Structural snapshots of plant-specific KCS6-CER2 complex reveal the elongation mechanism of very-long-chain fatty acids - Yang Wang; Haiyan Wang; Xianpeng Yang; Yujiao Qin; Rangwei Xu; Ting Liu; Chunmei Shi; Hongyan Zhang; Linlin Zhong; Xiaolu Qu; Feng Zhu; Xiuxin Deng; et al. (Molecular Plant, 2026)

The “Last-mile Efforts” of Subseasonal Prediction and Services for Climate Resilience and Sustainability: Review and Outlook - Jing Yang; Mengqian Lu; Anling Liu; Tat Fan Cheng; Yuxian Pan; Miaoni Gao; Lun Dai; Shentong Li; Wen Deng; Xinyao Feng; Shiyu Zhang; Lu Tang; et al. (Advances in Atmospheric Sciences, 2026)
Subseasonal predictions from 2 weeks to 2 months have made significant advancements over the past decade, driven by progress in physical understanding, climate modeling, computational capabilities, and artificial intelligence (AI). These predictions are increasingly in demand due to their potential to provide stakeholders with adequate lead time for effective disaster adaptation, mitigation, and resource management. However, there remain critical gaps in the engagement between prediction providers and service users. Providers often lack insight into the specific needs of users and do not have transferrable strategies to build trust through tailored evaluations and clear confidence levels, which often results in repeatedly devising approaches for each provider–user interaction. Further, users frequently struggle to interpret predictions and are hesitant to make decisions based on these uncertain outcomes. This paper attempts to make “last-mile efforts” by reviewing relevant literature, operational systems, and the most informative communications and engagement strategies with key sectors. It proposes a preliminary framework to standardize the approach for provider–user interaction in the context of subseasonal prediction and services, with potential applicability and extension to seamless prediction systems in the future. Lastly, we underscore future directions for subseasonal predictions, emphasizing the integration of dynamic climate modeling and AI-driven enhancements with large ensemble techniques to improve both reliability and confidence. This review is part of the United Nations Educational Scientific and Cultural Organization (UNESCO) International Decade of Sciences for Sustainable Development (2024–33) and contributes to the Seamless Prediction and Services for Sustainable Natural and Built Environment (SEPRESS) Program (2025–32), an initiative endorsed under this global framework.

Spatiotemporal distribution, source apportionment, and ecological risks of polycyclic aromatic hydrocarbons in surface water of the Southern Ocean - Tao Yang; Linlin Shi; Saizhang Tan; Bangping Deng; Yu Ke; Shengming Cheng; Yubin Li; Shuangcheng Zhang; Jingwei Wu; Lichen Zhao; Jun Shi (Frontiers in Marine Science, 2026)
In Antarctica, low temperatures favor the trapping and deposition of polycyclic aromatic hydrocarbons (PAHs), whereas the biogeochemical cycling of PAHs on the Southern Ocean adjacent to Antarctica is highly sensitive to climate change. However, very little environmental and ecological information is available on interannual PAHs variations in the surface of the Southern Ocean. From 2022 to 2024, we employed the 38 th , 39 th , and 40 th Chinese National Antarctic Research Expeditions (CHINARE) to collect surface water samples and conduct analyses of the spatio-temporal distribution patterns, source apportionment, and probabilistic ecological risk assessment of the 16 USEPA priority PAHs. We found that ∑PAH concentration in the study area ranged from 427 to 5782 pg/L, with median values of 1795, 1736, and 2559 pg/L for the 38 th , 39 th , and 40 th expeditions, respectively, showing a latitudinal gradient pattern of higher concentrations at lower latitudes and lower concentrations at higher latitudes. A significant concentration rebound was observed in the 40th expedition. Integrated analysis using molecular diagnostic ratios, PCA, and PMF revealed that this rebound was driven by a distinct “dual-pressure pattern”: intensified logistical traffic emissions (combustion sources) and the persistent release of fresh, unweathered PAHs. Source apportionment indicated an evolutionary trend from mixed petrogenic and ship-related liquid fuel combustion (38th) to episodic fresh local inputs (39th), culminating in the complex superposition of sources in the 40th survey. Probabilistic risk assessment using Monte Carlo simulations confirmed that acute risks to plankton remain low (the 95th percentile of ∑RQ MPC was 0.077); However, a structural shift towards hydrophobic high-molecular-weight PAHs (increasing to ~18% in 2024) signals a rising hidden potential for biomagnification in keystone species like Euphausia superba . These findings provide a critical scientific baseline for identifying pollution sources and supporting Antarctic ecosystem management under changing environmental conditions.

Penicinoid A, an undescribed sesterterpenoid with cytotoxic activity from Penicillium herquei - Mengyi Deng; Enrui Zhang; Fengtai Qiu; Yingying Fei; Yuyan Liu; Linlin Li; Yiyang Xiong; Xianli Zhou (Natural Product Research, 2026)

Climate and vegetation-driven variations, ecological thresholds and mechanisms of ecosystem services in China’s drylands - Baolong Ma; Linlin Gao; Yanjun Xu; Xinyue Li; Yang Deng; Haijiang Yang (Environment, Development and Sustainability, 2026)

Electronic structure tuning of Mn-based high-entropy spinel boosts benzene catalytic oxidation - Jiarui Chen; Xiaotong Li; Junjie Feng; Linlin Deng; Mingtai Li; Baojuan Dou; Feng Bin (Chemical Engineering Journal, 2026)

The intra-annual tree-ring δ18O records from the northeastern Tibetan Plateau can reflect seasonal variations of relative humidity and the intra-annual distribution of precipitation - Kai Wang; Xiaohua Gou; Takeshi Nakatsuka; Yiran Zhang; Tao Wang; Linlin Gao; Yang Deng; Zhen Li; Kaixuan Yang; Xuan Li; Chongshan Wang; Zibo Wang (Agricultural and Forest Meteorology, 2026)

Engineered microbial consortium enhances tomato salt tolerance through rhizosphere modulation for sustainable crop production - Linlin Sun; Xinyu Jia; Xiaohu Zhou; Junsong Yue; Zihe Deng; Muhammad Saad Ahmed; Xiaochen Liu; Zhansheng Wu (Journal of Cleaner Production, 2026)

Widespread vegetation damage in Asian Interior due to the 2022 extreme drought - Yu Luo; Linlin Gao; Xiyue Fu; Linhan Si; Xinyue Li; Na Du; Yiyun Yuan; Xiang Zhang; Yang Deng (Environmental Research, 2026)

Inhalable tetrahedral DNA nanoplatforms for dual-barrier penetration and sustained deep-lung delivery of small-molecule drugs - Fenglin Jiang; Qi Han; Hao Deng; Jiaqi Li; Alimire Alifu; Zhuo Chen; Linlin Deng; Xiaoxiao Cai; Yu Chen; Yunfeng Lin (Chemical Engineering Journal, 2026)

June–September mean temperature variability in the eastern Qinghai-Tibet Plateau over the past 225 years based on high quality tree-ring records - Xinyue Li; Linlin Gao; Baolong Ma; Kai Wang; Yang Deng (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Effect of salt stress-induced germination technology on the phenolic composition, antioxidant capacity, and metabolic pathways of highland barley (Hordeum vulgare L.): A metabolomics insight - Shuyao Wen; Disheng Xiao; Linlin Ye; Shimin Liu; Miao Liu; Xiaoyi Hou; Hui Li; Na Deng; Jianhui Wang (Food Bioscience, 2025)

Ginsenoside, a potential natural product against liver diseases: a comprehensive review from molecular mechanisms to application - Shiyan Shang; Haixia Yang; Linlin Qu; Daidi Fan; Jianjun Deng (Critical Reviews in Food Science and Nutrition, 2025)

Earlywood blue intensity of Picea purpurea reveals June minimum temperature variability in Eastern Tibetan Plateau since 1671CE - Na Du; Shuhua Qiao; Baolong Ma; Xinyue Li; Linhan Si; Linlin Gao; Yang Deng (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Coupled effects of riverbed topography and entrainment probability on bedload transport in the Middle Yangtze River - Linlin Li; Yu Lei; Junqiang Xia; Meirong Zhou; Shanshan Deng; Yao Xiao; Hang Li; Maohua Le (Acta Geophysica, 2025)

Boosting dynamic NH3 adsorption performance of UiO-66 via amino-induced local polarization - Zimu Liu; Mingtai Li; Zitong Zhao; Yulong Yang; Linlin Deng; Baojuan Dou; Feng Bin (Journal of Environmental Chemical Engineering, 2025)

An improved method for extracting cellulose from fossil wood and its paleoclimatic implications - Donghao Wu; Xin Wang; Yang Deng; Mi Wang; Gang Hu; Xuan Ding; Linlin Gao; Keyan Fang; Xiaohua Gou (Frontiers of Earth Science, 2025)

SagMSI: A graph convolutional network framework for precise spatial segmentation in mass spectrometry imaging - Mudassir Shah; Linlin Wang; Lei Guo; Chengyi Xie; Thomas Ka-Yam Lam; Lingli Deng; Xiangnan Xu; Jingjing Xu; Jiyang Dong; Zongwei Cai (Analytica Chimica Acta, 2025)

Promoting oxidation of high concentration CO via strong metal support interaction in unreduced Pt-based catalysts - Yulong Yang; Xiaokun Yi; Linlin Deng; Zitong Zhao; Zimu Liu; Mingtai Li; Baojuan Dou; Feng Bin (Journal of Environmental Chemical Engineering, 2025)

Inter-trophic networks reveal the central role of methanogens in deposited estuarine soils - Linlin Wang; Xiongfeng Du; Wenli Shen; Songsong Gu; Zhaojing Zhang; Zheng Zhang; Baohua Xie; Guangxuan Han; Ye Deng (Soil Ecology Letters, 2025)

Computational fluid dynamics and machine learning assisted Al-LDH adsorbent reactor design for lithium recovery from salt lakes - Jiangtao Yu; Minmeng Tang; Peng Cui; Jianquan Deng; Haiying Mi; Li Zhang; Linlin Chen; Peiwen Wu; Yanhong Chao; Wenshuai Zhu; Zhichang Liu (Desalination, 2025)

Correlation between the physicochemical and bacteriological qualities of pickled chili pepper (Paojiao) and its nitrite degradation study - Jianhui Wang; Miao Liu; Linlin Ye; Xiaoyi Hou; Zhenyu Li; Linzhi Tang; Na Deng; Hui Li (Food Bioscience, 2025)

Modeling of sediment exchange process and channel evolution in the downstream reach below the Three Gorges Dam - Linlin Li; Junqiang Xia; Meirong Zhou; Shanshan Deng; Defu Liu; Hang Li; Yu Lei (CATENA, 2025)

Rapid, green and semi-automated PT-μSPE for antidepressants analysis in urine and plasma using melt-blown polypropylene from disposable face masks as sorbent - Qianwei Li; Bowen Deng; Ru Feng; Di Chen; Linlin Hua (Sustainable Chemistry and Pharmacy, 2025)

Influence of atomic coordination on the activity of lattice oxygen and catalytic oxidation of toluene over regular Cu2O crystalline - Linlin Deng; Mingtai Li; Xin Gao; Xiaokun Yi; Yang Zhao; Yulong Yang; Zitong Zhao; Jiarui Chen; Baojuan Dou; Feng Bin (Journal of Hazardous Materials, 2025)

BDNF-VGF Pathway Aggravates Incision Induced Acute Postoperative Pain via Upregulating the Neuroinflammation in Dorsal Root Ganglia - Wenjing Zhao; Lulin Ma; Daling Deng; Linlin Han; Feng Xu; Tianhao Zhang; Yafeng Wang; Shiqian Huang; Yuanyuan Ding; Shaofang Shu; Xiangdong Chen (Molecular Neurobiology, 2025)

Numerical modeling of graded sediment transport with limited bed material supply – A case study in the Middle Yangtze River - Linlin Li; Junqiang Xia; Meirong Zhou; Shanshan Deng; Jie Li; Yao Xiao (Journal of Hydrology, 2024)

Ultrasensitive monitoring of PCB77 in environmental samples using a visible-driven photoelectrochemical sensing platform coupling with exonuclease I assisted in target recycling - Lining Su; Guizhen Wang; Linlin Zhao; Yuan Deng; Yujing Guo; Yong Xiao; Huanwen Wang; Chuan Dong; Lifang Fan (Science of The Total Environment, 2024)

Finer topographic data improves distribution modeling of Picea crassifolia in the northern Qilian Mountains - Xiang Zhang; Linlin Gao; Yu Luo; Yiyun Yuan; Baolong Ma; Yang Deng (Journal of Mountain Science, 2024)

Elevated lead mobility in sediments of a eutrophic drinking water reservoir during spring and summer seasons: Insights from isotopic signatures - Zhenghua Tao; Guogan Peng; Fengyuan Chen; Qingjun Guo; Rongfei Wei; Ke Pan; Yinan Deng; Linlin Jiao; Zhen Zhang; Shanshan Chen; Tianxiang Xia (Journal of Hazardous Materials, 2024)

Unprecedented recent warming as recorded by tree-ring in the western Qinling Mountains, China - Yiyun Yuan; Yang Deng; Linlin Gao; Xiyue Fu; Yanjun Xu; Xiaohua Gou (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Seasonal aridity regulates drivers and temporal variability of wood phenology: A meta-analysis of dendrometer monitoring data across the Northern Hemisphere - Yuhang Zhang; Linlin Gao; Yang Deng; Qianling Huang; Yiyun Yuan; Xingying Shi; Xiaohua Gou (Dendrochronologia, 2024)

A tree-ring based streamflow reconstruction for the Taohe River (Gannan Plateau, China) associated with the Asian-Pacific Oscillation since 1325 CE - Xingying Shi; Linlin Gao; Yang Deng; Yuhang Zhang; Xiang Zhang; Xiaohua Gou (CATENA, 2024)

Rapid Diagnosis of Pneumocystis jirovecii Pneumonia and Respiratory Tract Colonization by Next-Generation Sequencing - Fanfan Xing; Chaowen Deng; Zhendong Luo; Shan Zou; Min Liu; Haiyan Ye; Linlin Sun; Chi-Ching Tsang; Simon K. F. Lo; Susanna K. P. Lau; Patrick C. Y. Woo (Mycopathologia, 2024)
Objectives To describe the epidemiology of Pneumocystis jirovecii pneumonia and colonization diagnosed by next-generation sequencing (NGS) and explore the usefulness of the number of P. jirovecii sequence reads for the diagnosis of P. jirovecii pneumonia. Methods We examined the NGS results for P. jirovecii in respiratory samples collected from patients and analysed their clinical, radiological and microbiological characteristics. Results Among 285 respiratory samples collected over a 12-month period (January to December 2022), P. jirovecii sequences were detected in 56 samples from 53 patients. Fifty (94.3%) of the 53 patients were HIV-negative. Following our case definitions, 37 (69.8%) and 16 (30.2%) of the 53 patients had P. jirovecii infection and colonization respectively. P. jirovecii infection was associated with presence of underlying disease with immunosuppression (94.6% vs 18.8%, P < 0.05), positive serum 1,3-β-D-glucan (41.2% vs 0%, P < 0.01) and higher number of P. jirovecii sequence reads ( P < 0.005). In contrast, P. jirovecii colonization was associated with the male sex (93.8% vs 54.1%, P < 0.01), another definitive infectious disease diagnosis of the respiratory tract (43.8% vs 2.7%, P < 0.001) and higher survival (100% vs 67.6%, P < 0.01). Although P. jirovecii pneumonia was associated with higher number of P. jirovecii reads in respiratory samples, only a sensitivity of 82.14% and a specificity of 68.75% could be achieved. Conclusion Detection of P. jirovecii sequences in respiratory samples has to be interpreted discreetly. A combination of clinical, radiological and laboratory findings is still the most crucial in determining whether a particular case is genuine P. jirovecii pneumonia.

A comprehensive “quality-quantity-activity” approach based on portable near-infrared spectrometer and membership function analysis to systematically evaluate spice quality: Cinnamomum cassia as an example - Ziwei Zou; Bingjian Guo; Yue Guo; Xiaolong Ma; Sanshan Luo; Linlin Feng; Ziping Pan; Lijun Deng; Shihan Pan; Jinbin Wei; Zhiheng Su (Food Chemistry, 2024)

Dominant contribution of combustion-related ammonium during haze pollution in Beijing - Libin Wu; Peng Wang; Qiang Zhang; Hong Ren; Zongbo Shi; Wei Hu; Jing Chen; Qiaorong Xie; Linjie Li; Siyao Yue; Lianfang Wei; Linlin Song; et al. (Science Bulletin, 2024)

Asymmetric impacts of El Niño-Southern Oscillation on summer temperature over the eastern Qinghai-Tibetan Plateau, as revealed by the blue intensity of Picea purpurea - Shuhua Qiao; Yang Deng; Linlin Gao; Yiyun Yuan; Qianling Huang; Xiaohua Gou (Global and Planetary Change, 2024)

Long-Term Effects of Ecological Restoration Projects on Ecosystem Services and Their Spatial Interactions: A Case Study of Hainan Tropical Forest Park in China - Jiahui Zhong; Linlin Cui; Zhiyin Deng; Yong Zhang; Jie Lin; Geng Guo; Xiang Zhang (Environmental Management, 2024)

A two-centennial perspective on spatially compounding hydroclimate events in arid and semi-arid north China - Qian Li; Linlin Gao; Yang Deng; Xiang Zhang; Yongkang Duan; Xiaohua Gou (Quaternary Science Reviews, 2023)

The effects of selenium on the growth and bone development in the weaned rats - Hongan Li; Linlin Jia; Zeyuan Deng; Xiaomao Sun; Hui Zhang; Hongyan Li (Food Bioscience, 2023)

An ultra-stable high entropy metal nitride for aerobic oxidative desulfurization and source recovery of aromatic sulfides from fuel oils - Peiwen Wu; Chang Deng; Penghui Liu; Feng Liu; Linlin Chen; Bangzhu Wang; Wenshuai Zhu; Chunming Xu (Chemical Engineering Journal, 2023)

Targeted preparation of biochar for the application as composting additive: Influence mechanism of feedstock properties on biochar derived from traditional Chinese herb residue - Haoyu Tang; Aijun Li; Linlin Yi; Yongda Huang; Qian Deng; Yangwei Wu; Hong Yao (Process Safety and Environmental Protection, 2023)

Influence of monsoon anomalies on intra-annual density fluctuations of Chinese pine in the Loess Plateau - Shuangjuan Wang; Yang Deng; Linlin Gao; Yuhang Zhang; Xingying Shi; Xiaohua Gou (International Journal of Biometeorology, 2023)

Environmental DNA metabarcoding reveals the influence of human activities on microeukaryotic plankton along the Chinese coastline - Zheng Zhang; Jiang Li; Hongjun Li; Linlin Wang; Yuqi Zhou; Shuzhen Li; Zhaojing Zhang; Kai Feng; Ye Deng (Water Research, 2023)

The structural characterization of polysaccharides from three cultivars of Moringa oleifera Lam. root and their effects on human intestinal microflora - Linlin Jia; Xiaoqiang Peng; Zeyuan Deng; Bing Zhang; Hongyan Li (Food Bioscience, 2023)

Spatial distribution patterns across multiple microbial taxonomic groups - Xiongfeng Du; Songsong Gu; Zheng Zhang; Shuzhen Li; Yuqi Zhou; Zhaojing Zhang; Qi Zhang; Linlin Wang; Zhicheng Ju; Chengliang Yan; Tong Li; Danrui Wang; et al. (Environmental Research, 2023)

Pre-monsoon drought variability in the southeastern Loess Plateau over the past 246 years - Yongkang Duan; Shuangjuan Wang; Yang Deng; Linlin Gao; Shuhua Qiao; Xiaohua Gou (Quaternary International, 2023)

Acrylamide Induces Neurotoxicity in SH-SY5Y Cells via NLRP3-mediated Pyroptosis - Mengyao Zhao; Boya Zhang; Linlin Deng; Liming Zhao (Molecular Neurobiology, 2023)

Methylmercury promotes oxidative stress and autophagy in rat cerebral cortex: Involvement of PI3K/AKT/mTOR or AMPK/TSC2/mTOR pathways and attenuation by N-acetyl-L-cysteine - Yanfeng Wei; Linlin Ni; Jingjing Pan; Xiaoyang Li; Yu Deng; Bin Xu; Tianyao Yang; Jingyi Sun; Wei Liu (Neurotoxicology and Teratology, 2023)

TRIM11, a new target of p53, facilitates the migration and invasion of nasopharyngeal carcinoma cells - Ziyi Zhao; Jinkuang Deng; Ming Lu; Jun Yang; Linlin Chen; DianYuan Li; Yi Sang (Molecular Biology Reports, 2023)
Background Although tripartite motif-containing protein 11 (TRIM11) is known to be associated with a variety of cancers, its role in nasopharyngeal carcinoma (NPC) is unclear. Methods and results To investigate the role of TRIM11 in NPC, TRIM11 was stably overexpressed in 6–10B and CNE2 cells with lentiviral vectors and knocked down in S18 and 5–8F cells using the CRISPR/Cas9 system. Transwell assays and wound-healing assays revealed that TRIM11 facilitated the migration and invasion of NPC cells. Mechanistically, we found that p53 inhibits TRIM11 expression by binding to its promoter. Conclusions TRIM11 may serve as a potential diagnostic marker for NPC and has a certain therapeutic value.

Structural and functional analysis of a potent human neutralizing antibody against enterovirus A71 - Zhe Chen; Linlin Bao; Bin Zhu; Hua Fu; Shuangli Zhu; Tianjiao Ji; Ying Xue; Chuan Liu; Xurong Wang; Fengdi Li; Qi Lv; Feifei Qi; et al. (Science China Life Sciences, 2022)

Improving precipitation ensemble forecasts of typhoon heavy rainfall over East China with a modified probability-matching technique - Chun Liu; Hanqing Deng; Xuexing Qiu; Linlin Zheng; Yajun Lu; Ying Zhang (Bulletin of Atmospheric Science and Technology, 2022)

The involvement of oxidative stress, neuronal lesions, neurotransmission impairment, and neuroinflammation in acrylamide-induced neurotoxicity in C57/BL6 mice - Mengyao Zhao; Linlin Deng; Xiaoxuan Lu; Liqiang Fan; Yang Zhu; Liming Zhao (Environmental Science and Pollution Research, 2022)

Warming reshaped the microbial hierarchical interactions - Yuqi Zhou; Baoyu Sun; Baohua Xie; Kai Feng; Zhaojing Zhang; Zheng Zhang; Shuzhen Li; Xiongfeng Du; Qi Zhang; Songsong Gu; Wen Song; Linlin Wang; et al. (Global Change Biology, 2021)
Global warming may alter microbially mediated ecosystem functions through reshaping of microbial diversity and modified microbial interactions. Here, we examined the effects of 5‐year experimental warming on different microbial hierarchical groups in a coastal nontidal soil ecosystem, including prokaryotes (i.e., bacteria and archaea), fungi, and Cercozoa, which is a widespread phylum of protists. Warming significantly altered the diversity and structure of prokaryotic and fungal communities in soil and additionally decreased the complexity of the prokaryotic network and fragmented the cercozoan network. By using the Inter‐Domain Ecological Network approach, the cross‐trophic interactions among prokaryotes, fungi, and Cercozoa were further investigated. Under warming, cercozoan–prokaryotic and fungal–prokaryotic bipartite networks were simplified, whereas the cercozoan–fungal network became slightly more complex. Despite simplification of the fungal–prokaryotic network, the strengthened synergistic interactions between saprotrophic fungi and certain prokaryotic groups, such as the Bacteroidetes, retained these phyla within the network under warming. In addition, the interactions within the fungal community were quite stable under warming conditions, which stabilized the interactions between fungi and prokaryotes or protists. Additionally, we found the microbial hierarchical interactions were affected by environmental stress (i.e., salinity and pH) and soil nutrients. Interestingly, the relevant microbial groups could respond to different soil properties under ambient conditions, whereas under warming these two groups tended to respond to similar soil properties, suggesting network hub species responded to certain environmental changes related to warming, and then transferred this response to their partners through trophic interactions. Finally, warming strengthened the network modules’ negative association with soil organic matters through some fungal hub species, which might trigger soil carbon loss in this ecosystem. Our study provides new insights into the response and feedback of microbial hierarchical interactions under warming scenario.

Late Eocene sclerophyllous oak from Markam Basin, Tibet, and its biogeographic implications - Linlin Chen; Weiyudong Deng; Tao Su; Shufeng Li; Zhekun Zhou (Science China Earth Sciences, 2021)

Constitutive activation of β-catenin in odontoblasts induces aberrant pulp calcification in mouse incisors - Shijian Deng; Linlin Fan; Yunfei Wang; Qi Zhang (Journal of Molecular Histology, 2021)

miR-146a-3p suppressed the differentiation of hAMSCs into Schwann cells via inhibiting the expression of ERBB2 - Wei Chen; Linlin Ji; Zairong Wei; Chenglan Yang; Shusen Chang; Yucheng Zhang; Kaiyu Nie; Lingli Jiang; Yurong Deng (Cell and Tissue Research, 2021)
Human amniotic mesenchymal stem cells (hAMSCs) can be differentiated into Schwann-cell-like cells (SCLCs) in vitro. However, the underlying mechanism of cell differentiation remains unclear. In this study, we explored the phenotype and multipotency of hAMSCs, which were differentiated into SCLCs, and the expression of nerve repair-related Schwann markers, such as S100 calcium binding protein B (S-100), TNF receptor superfamily member 1B (P75), and glial fibrillary acidic protein (GFAP) were observed to be significantly increased. The secreted functional neurotrophic factors, like brain-derived neurotrophic factor (BDNF), nerve growth factor (NGF), and neurotrophin-3 (NT-3), were determined and also increased with the differentiation time. Moreover, miR-146a-3p, which significantly decreased during the differentiation of hAMSCs into SCLCs, was selected by miRNA-sequence analysis. Further molecular mechanism studies showed that Erb-B2 receptor tyrosine kinase 2 (ERBB2) was an effective target of miR-146a-3p and that miR-146a-3p down-regulated ERBB2 expression by binding to the 3′-UTR of ERBB2. The expression of miR-146a-3p markedly decreased, while the mRNA levels of ERBB2 increased with the differentiation time. The results showed that down-regulating miR-146a-3p could promote SC lineage differentiation and suggested that miR-146a-3p negatively regulated the Schwann-like phenotype differentiation of hAMSCs by targeting ERBB2. The results will be helpful to establish a deeper understanding of the underlying mechanisms and find novel strategies for cell therapy.

Utilization of serum procalcitonin as a biomarker in the diagnosis and treatment of children with bacterial hospital-acquired pneumonia - Wenlong Wang; Yitang Zhu; Linlin Yin; Yaoyao Deng; Guoxian Chu; Supin Liu (Molecular and Cellular Biochemistry, 2021)

Multi‐century drought variability in the southern Min Mountains - Xiaoya Yan; Yang Deng; Haowen Fan; Jiajia Su; Linlin Gao; Xiaohua Gou (International Journal of Climatology, 2020)
Information on moisture variability is important for climate adaptation and planning, which is urgently needed for the Jiuzhaigou County after it was hit by a magnitude 7.0 earthquake in August 2017, resulting in potential interactions between the earth surface processes and the hydroclimate. To study the regional hydroclimatic history beyond instrumental records, the first tree‐ring hydroclimate reconstruction, based on Pinus tabuliformis , was conducted in the southern Min Mountains, which is situated close to the areas affected by the Jiuzhaigou earthquake. The reconstruction, spanning from 1684 to 2017, explained 59% of the variance for May–August standardized precipitation evapotranspiration index at a 12‐month scale during 1962–2017. The recent drought, which occurred from 1992 to 2017 was the longest in duration, largest in magnitude, and had the second highest intensity. The most severe single year drought occurred in 1824, which was lower than the long‐term mean by 4 σ and affected several regions in and around the Northeast Qinghai‐Tibet Plateau. The drought reconstruction was consistent with other moisture reconstructions, but dissimilar were also exist during some periods. There was a significant correlation between drought reconstruction and sea surface temperature over many oceans. However, the correlations were unstable over time. This study suggests the importance of developing a density tree‐ring network to identify the spatial and temporal drought variability, as well as long‐term record for understanding regional climate dynamics.

Riverbed armoring and sediment exchange process in a sand–gravel bed reach after the Three Gorges Project operation - Linlin Li; Junqiang Xia; Meirong Zhou; Shanshan Deng (Acta Geophysica, 2020)

Assessment of the effects of lethal and sublethal exposure to dinotefuran on the wheat aphid Rhopalosiphum padi (Linnaeus) - Denghui Deng; Wenbo Duan; Hao Wang; Kun Zhang; Jianglong Guo; Linlin Yuan; Likui Wang; Shaoying Wu (Ecotoxicology, 2019)

Ozonation catalyzed by iron- and/or manganese-supported granular activated carbons for the treatment of phenol - Wei Xiong; Nan Chen; Chuanping Feng; Yang Liu; Ningping Ma; Jian Deng; Linlin Xing; Yu Gao (Environmental Science and Pollution Research, 2019)

Sodium Fluoride (NaF) Induces Inflammatory Responses Via Activating MAPKs/NF-κB Signaling Pathway and Reducing Anti-inflammatory Cytokine Expression in the Mouse Liver - Linlin Chen; Ping Kuang; Huan Liu; Qin Wei; Hengmin Cui; Jing Fang; Zhicai Zuo; Junliang Deng; Yinglun Li; Xun Wang; Ling Zhao (Biological Trace Element Research, 2019)

Constitutive activation of β-catenin in ameloblasts leads to incisor enamel hypomineralization - Linlin Fan; Shijian Deng; Xin Sui; Mengmeng Liu; Shuhua Cheng; Yunfei Wang; Yuguang Gao; Chun-Hung Chu; Qi Zhang (Journal of Molecular Histology, 2018)

Osteoprotegerin deficiency causes morphological and quantitative damage in epithelial rests of Malassez - Yunfei Wang; Mengmeng Liu; Shijian Deng; Xin Sui; Linlin Fan; Qi Zhang (Journal of Molecular Histology, 2018)

The role of Ustilaginoidea virens sclerotia in increasing incidence of rice false smut disease in the subtropical zone in China - Mingli Yong; Qide Deng; Linlin Fan; Jiankun Miao; Chaohui Lai; Hongming Chen; Xiujuan Yang; Shu Wang; Furu Chen; Li Jin; Binghui Yang; Yuanjun Bai; et al. (European Journal of Plant Pathology, 2018)

Spatiotemporal drought variability of the eastern Tibetan Plateau during the last millennium - Yang Deng; Xiaohua Gou; Linlin Gao; Meixue Yang; Fen Zhang (Climate Dynamics, 2017)

Assessing the influences of tree species, elevation and climate on tree-ring growth in the Qilian Mountains of northwest China - Linlin Gao; Xiaohua Gou; Yang Deng; Meixue Yang; Fen Zhang (Trees, 2017)

Tree‐ring recorded drought variability in the northern Min Mountains of northwestern China - Yang Deng; Xiaohua Gou; Linlin Gao; Fen Zhang; Xiangyu Xu; Meixue Yang (International Journal of Climatology, 2016)
Drought is a recurrent natural disaster in northwestern China and it can have a substantial impact on the affected region; therefore, knowledge of drought variability is very important for drought adaptation and mitigation. However, the observed climate data are generally limited in length, which may hamper our understanding the full range of drought variability. Using tree‐ring width measurements of 155 series from 81 Pinus tabulaeformis trees at three sites in the northern Min Mountains of northwestern China, the standardized precipitation evapotranspiration index ( SPEI ) for May–August from 1804 to 2011 were reconstructed, which account for 64.8% of the variance in the instrumental record over 1954–2011. The new reconstruction is generally consistent with other moisture reconstructions nearby. Two notable features of the SPEI reconstruction is the severe drought starting in the late 1990s and the gradual drying trend since 1954. These features are also apparent in areas located in the north boundaries of Eastern Asian Summer Monsoon ( EASM ), which indicates that the study area may be affected by the EASM .

Millennium tree-ring reconstruction of drought variability in the eastern Qilian Mountains, northwest China - Xiaohua Gou; Yang Deng; Linlin Gao; Fahu Chen; Edward Cook; Meixue Yang; Fen Zhang (Climate Dynamics, 2015)

An 850‐year tree‐ring‐based reconstruction of drought history in the western Qilian Mountains of northwestern China - Xiaohua Gou; Linlin Gao; Yang Deng; Fahu Chen; Meixue Yang; Christopher Still (International Journal of Climatology, 2015)
Studies of regional drought history will be helpful for understanding current hydroclimate variability with global warming as well as predicting future hydroclimate shifts. Long‐term tree‐ring records are scarce in the western Qilian Mountains of northwestern China, which is also the western boundary of the natural distribution of Qilian Juniper ( Juniperus przewalskii Kom.) in this area. Here, we present an 850‐year ( AD 1161 –2010) reconstruction of May–July self‐calibrating Palmer Drought Severity Index ( scPDSI ) in the western Qilian Mountains that is based on two nearly millennia of ring‐width chronologies derived from long‐lived Qilian Juniper trees. The reconstruction suggests a relatively dry phase from the 15th century to the 18th century during the Little Ice Age ( LIA ) and a relatively wet period over the past two centuries. This reconstruction is consistent with other tree‐ring‐based hydroclimatic reconstructions from the northeastern Tibetan Plateau, as well as the corresponding century‐scale solar activity during the LIA . The three mega‐drought periods ( AD 1260s –1340s, 1430s–1540s and 1640s–1740s) recorded by the tree‐ring series also correspond to the Wolf, Spörer and Maunder solar activity minimum periods. Results of the multi‐tape method analysis and wavelet analysis further confirmed the relationship between regional hydroclimate variability and solar activity forcing.

A gyrovirus infecting a sea bird - Linlin Li; Patricia A. Pesavento; Anne M. Gaynor; Rebecca S. Duerr; Tung Gia Phan; Wen Zhang; Xutao Deng; Eric Delwart (Archives of Virology, 2015)

Distribution of enterovirus 71 RNA in inflammatory cells infiltrating different tissues in fatal cases of hand, foot, and mouth disease - Pin Yu; Zifen Gao; Yuanyuan Zong; Linlin Bao; Lili Xu; Wei Deng; Yanfeng Xu; Zhancheng Gao; Yanfeng Yao; Fengdi Li; Qi Lv; Chuan Qin (Archives of Virology, 2015)

Climate–growth analysis of Qilian juniper across an altitudinal gradient in the central Qilian Mountains, northwest China - Linlin Gao; Xiaohua Gou; Yang Deng; Wenhuo Liu; Meixue Yang; Zhiqian Zhao (Trees, 2013)

Expression of phytoene synthase gene (Psy) is enhanced during fruit ripening of Cara Cara navel orange (Citrus sinensis Osbeck) - Nengguo Tao; Zhiyong Hu; Qin Liu; Juan Xu; Yunjiang Cheng; Linlin Guo; Wenwu Guo; Xiuxin Deng (Plant Cell Reports, 2007)